Study of the ISO-FDTD algorithm for processing higher-order dielectric function in SF-FDTD - Gu, Ke-Da; Xie, Jin; Yang, Hong-Wei (Journal of computational electronics, 2024)
We use an improved shift operator finite-difference time-domain (ISO-FDTD) algorithm, previously proposed by others, to further process more complex dielectric functions including critical models and several higher-order Lorentz models that we fitted ourselves. These function models have a total of 6–8 sub-terms, and each sub-term consists of two complex poles (Lorentz model). This work supports the universal applicability of the ISO-FDTD algorithm for processing higher-order complex dispersive materials. We applied this ISO-FDTD algorithm in split-field FDTD (SF-FDTD) to simulate dispersion media under oblique incidence. The simulation results agree well with the analytical solutions. Thus, this approach provides researchers with an alternative option apart from auxiliary differential equations (ADE) or piecewise linear recursive convolution (PLRC) methods when processing high-order dispersive media in SF-FDTD.